Ability within disability: Reflective memories shared with Dr Kasturi Varley - Archary, Kogielam K. (HTS teologiese studies, 2022)
In a post-apartheid South Africa, the value of reflective memories and their impact on community history gives credibility to their relationship with personal struggles such as disability, be it physical or political. Shaped by South African Indian heritage, an isolated individualised case of a second-generation descendant’s ability–disability experience is researched and narrated in this article. The respondent, Dr Kasturi Varley is a woman of the South African Indian community, who was born almost 101 years after the first shipload of Indian indentured labourers arrived in the then Colony of Natal. Her memories shed light on a unique Indo-African-European experience. Her indentured paternal grandfather arrived in the African continent in August 1900. Her reflective memories and shared experiences of various episodes of the ability–disability paradigm add to the body of knowledge of the Indian indentured labour system that already exists and partially fills up the prevalent gaps in the research on this topic. Her story is unique in that she worked wheelchair-bound at the International Atomic Energy Agency in Vienna, Austria and subsequently settled in the United Kingdom. This study applied a qualitative research methodology.Contribution: This article provides insight on reflective memories within the domain of social memory and contributes to an understanding of the historiography of the descendants of Indian indentured labourers in South Africa. In 2020, this community commemorated the 160th anniversary of the arrival of the labourers to the Colony of Natal.